Assessment of the population’s social resilience environment (the case of the Carpathian region of Ukraine) - Olha Mulska; Taras Vasyltsiv; Yuliia Shushkova; Lev Kloba; Yevheniya Parfenyuk (Problems and Perspectives in Management, 2022)
The system of indicators of the population’s socio-economic vulnerability is the determinant of regions’ social resilience. The growth of these indicators leads to the emergence of new and aggravation of existing social risks and threats in different time periods. The paper aims to provide a comprehensive assessment of the population’s social resilience environment in the Carpathian region of Ukraine. The environment of the population social resilience in the oblasts of the Carpathian region of Ukraine is assessed based on the theory of elasticity by calculating the temporal weight coefficients of 31 indicators (systematized in 4 groups) and integral empirical coefficient of the environment by multiplicative assessment. The results show that among the oblasts of the Carpathian region of Ukraine, the social resilience environment was the highest in Zakarpatska and Ivano-Frankivska oblasts (0.530 each) in 2019, and in Lvivska (0.540) and Chernivetska (0.585) oblasts in 2014. The growth of the social resilience environment rate was recorded in Lvivska (0.630) and Chernivetska (0.691) oblasts in the period of economic capacity recovery (2018). The average annual growth pace of the coefficient of deviation of the empirical social resilience environment rate from the national rate ranged from –1.29% to –0.26%. The study can serve as an information-analytical basis for developing the regional policy to secure the convergence of social standards of social resilience between the Carpathian region and neighboring EU countries (adherence to the principles of consumption safety and social responsibility, growing resistance of the healthcare system, balanced labor market and employment, development of clean and safe living spaces). AcknowledgmentThe study was conducted within the framework of applied research “Mechanisms of the proactive policy for reducing social vulnerability of the population (based on the Carpathian region of Ukraine)” (No SR 0121U112014, M. Dolishniy Institute of Regional Research of National Academy of Sciences of Ukraine, 2021–2023).